National Media Framing of Indonesia’s Accession to the Board of Peace - Imas Ananta Efendi; Wahyu Dwi Pambagyo (Dauliyah Journal of Islamic and International Affairs, 2026)
This study examines the framing by Indonesian national media of Indonesia's decision to join the Board of Peace (BoP) as a novel diplomatic avenue concerning the Gaza issue. This study used a qualitative-descriptive methodology utilizing NVivo for matrix coding queries to analyze the tone of news coverage (positive, neutral, negative) and its implications for the formulation of foreign policy meaning. The research results indicate distinct differences in framing among media channels. Kompas predominantly adopts a positive tone, which reinforces the legitimacy of the government's actions as “advocacy from within” and underscores its ongoing pro-Palestinian stance. Tempo exhibits a more moderate tone, suggesting a propensity for careful and informative reporting regarding the prospects and institutional ramifications of BoP. The Jakarta Post exhibits a greater degree of balance, presenting a conflict between narratives of potential influence and apprehensions regarding normative hazards. These findings affirm that Indonesia's membership to BoP serves as a platform for the generation of contentious interpretations within the domestic media landscape.